PENENTUAN HARGA POKOK PENJUALAN KAMAR â€œDELUXEâ€ DENGAN MENGGUNAKAN METODE ACTIVITY BASED COSTING PADA RESORT G-LAND JOYOâ€™S CAMP TAHUN 2010 - PUTIKADEA, INSYIRAH (Jurnal Akuntansi AKUNESA, 2012)
Implemetation of ABC can resulting cost of sales more accurate and minimize distortion of costs. Object of this research is “Deluxe Room” G-Land Joyo’s Camp. This result shows cost of sales “Deluxe Room” on ABC method more less than convensional method that implemented by company, with diferrences Rp 155.715,74. It’s because convensional method charges all costs on product while on ABC method costs are charging on product by activities that consumed.Keywords : Activity Based Costing, ABC, Resort, Cost Driver